Eskalasi Peran Gen Z Dalam Melawan Kekerasan Seksual di Tengah Masyarakat Madani - Fajri, Pujangga Candrawijayaning; Hesti Ayu Wahyuni; Monica Puspa Dewi (Nusantara Mengabdi Kepada Negeri, 2025)
This community service article aims to escalate Gen Z's understanding of sexual violence, which continues to show a concerning trend in case numbers, thereby hindering the nation's aspirations towards a civil society. The cause of the high trend in sexual violence is that victims do not yet understand the content of the TPKS Law; the reporting mechanism and the legal process in court. Considering that the effectiveness of the law cannot be sufficiently realized through adequate content and means (legal substance-legal structure), efforts are needed through the work of other variables, such as community involvement (legal culture), which in this service activity is carried out and participated in by students from SMA Negeri 1 Wangon. The method used in this program is lectures and interactive discussions. The result of this program is a comprehensive understanding of the TPKS Law, which is then followed by building a commitment to combat sexual violence through daily campaigns, both in the form of preventive and repressive actions carried out in social-community environments and on social media. So that the aspiration for the formation of a civil society can be realized.